Restoratif Justice In the Perspective of Customary Law: A Solution to the Settlement of Narcotics Crimes Commited by Children - Badu, Lisnawaty Wadju; Kaluku, Julisa Aprilia (Jambura Law Review, 2022)
Restorative Justice is a thought that responds to the development of the criminal justice system by focusing on the needs of the community, where the settlement uses customary law which is something that is very urgent at this time by considering various things besides so that the settlement does not take a long time, but also the parties do not incur large costs and the most important thing is that family relations will remain harmoniously intertwined so as not to leave the problem of "revenge" for their descendants, especially for children who are involved in narcotics crimes, considering that children can become victims of adult behavior. The re-establishment of harmony in social ties of course will maintain public security and order. The method in this research is field research or often called Empirical Law research, namely research that looks directly at the reality in the field, this type of research has the nature and character of showing the gap between the applicable law and the existing reality. One solution that is carried out on the concept of restorative justice is to divert or place the perpetrators of child crimes out of the criminal justice system, meaning that not all cases of juvenile delinquents must be resolved through formal justice, and provide an alternative for settlement with a justice approach in the best interest of for children.